Secondary Cancer after Androgen Deprivation Therapy in Prostate Cancer: A Nationwide Study - Jae Heon Kim; Gi Hwan Bae; Jaehun Jung; Tae Il Noh (The World Journal of Men's Health)
Purpose: Androgen signaling is associated with various secondary cancer, which could be promising for potential treatment using androgen deprivation therapy (ADT). This study investigated whether ADT use was associated with secondary cancers other than prostate cancer in a nationwide population-based cohort. Materials and Methods: A total, 278,434 men with newly diagnosed prostate cancer between January 1, 2002 and December 31, 2017 were identified. After applying the exclusion criteria, 170,416 men were enrolled. The study cohort was divided into ADT and non-ADT groups by individual matching followed by propensity score matching (PSM). Study outcomes were incidence of all male cancers. Cox proportional hazard regression models were used to estimate adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) of events. Results: During a median follow-up of 4.5 years, a total of 11,059 deaths (6,329 in the ADT group and 4,730 in the non- ADT group) after PSM were found. After PSM, the overall all-cause of secondary cancer incidence risk of the ADT group was higher than that of the non-ADT group (HR: 1.312, 95% CI: 1.23–1.36; adjusted HR: 1.344, 95% CI: 1.29–1.40). The ADT group showed higher risk of overall brain and other central nervous system (CNS) cancer-specific incidence than the non- ADT group (adjusted HR: 1.648, 95% CI: 1.21–2.24). The ADT group showed lower risks of overall cancer-specific incidence for stomach, colon/rectum, liver/inflammatory bowel disease (IBD), gall bladder/extrahepatic bile duct, lung, bladder, and kidney cancers than the non-ADT group. When the duration of ADT was more than 2 years of ADT, the ADT group showed higher risk of cancer-specific incidence for brain and other CNS cancers but lower risk of cancer-specific incidence for liver/ IBD and lung cancers than the non-ADT group. Conclusions: This study demonstrates that ADT could affect cancer-specific incidence for various cancers.